PERLINDUNGAN HUKUM BAGI KONSUMEN AKIBAT PRICE FIXING AGREEMENT PADA TARIF ANGKUTAN UDARA YANG MENYEBABKAN PERSAINGAN USAHA TIDAK SEHAT - Ulya, Rahmatul; Rahmayani, Nuzul; Adriaman, Mahlil (The Juris, 2023)
A price fixing agreement is an agreement practice entered into by companies in the same industry to fix prices for goods/services together in the relevant market. Price fixing agreements on air freight rates have a negative impact on business competition, especially for consumers who use air transport services. This study aims to determine the form of price fixing agreement practices on air freight rates and the form of legal protection for consumers against price fixing agreements on air freight rates. This research uses normative legal research methods through literature study. The results of this study indicate that business actors who enter into price fixing agreements to increase the price of airplane tickets beyond the specified tarif limit have violated the provisions of business competition law, which can harm consumers. The legal protection provided to consumers in the form of preventive legal protection and repressive legal protection depends on the jurisdiction and the applicable legal framework.